2023
DOI: 10.3390/children10030471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tooth Brushing and Previous Dental Visits on Dental Caries Status among Saudi Arabian Children

Abstract: Objective: To evaluate the dental caries status and its association with tooth brushing frequency and previous dental visits among Arabian children. Methods: Arabian school children attend a specialty pediatric dental clinic at Majmaah University, Saudi Arabia. Only children of Saudi origin with primary dentition were included in the study, and only one examiner was involved in the assessment and data collection. The parents of children completed a questionnaire to investigate possible explanatory variables fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
4
4
1
1
Order By: Relevance
“…[35] also reported that students who had never brushed their teeth or done is so infrequently had scored higher DMFT results opposite to those who brushed their teeth at least once and more. Furthermore contrary to our results, other studies made by [36], observed no correlation between caries and frequency of tooth brushing. This might be related to improper technique of brushing and not enough tooth brushing time and low level of fluoride in toothpaste.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[35] also reported that students who had never brushed their teeth or done is so infrequently had scored higher DMFT results opposite to those who brushed their teeth at least once and more. Furthermore contrary to our results, other studies made by [36], observed no correlation between caries and frequency of tooth brushing. This might be related to improper technique of brushing and not enough tooth brushing time and low level of fluoride in toothpaste.…”
Section: Discussioncontrasting
confidence: 99%
“…33%) and 67 of them used to have dental visits only if necessary (55. 83%) there is a positive significant correlation between this category and DMFT increase, our results are in accordance with previous researches from [33,36] which reported a positive link between dental visits and caries.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, age was significantly associated with ECC, where older children had higher odds of having ECC. This agrees with several previous research [ 3 , 22 , 23 ], which could be attributed to the increasing number of erupted primary teeth, and teeth becoming more exposed to the oral environment and various cariogenic challenges. Study findings revealed that mother’s education was significantly associated with ECC, and father’s employment status was not associated with the presence of ECC.…”
Section: Discussionsupporting
confidence: 93%
“…The study investigated a number of oral health habits. Among them, toothbrushing was not significantly associated with the presence of ECC, this finding agrees with Mallineni et al [ 23 ]. This may be due to the fact that preschool children may lack the manual dexterity required to remove dental plaque and maintain good oral hygiene, therefore, no difference was found regarding ECC between children who brushed their teeth and those who did not.…”
Section: Discussionsupporting
confidence: 91%
“…Melalui demonstrasi, peserta dapat memahami secara praktis bagaimana menyikat gigi dengan benar. Ini membantu dalam memperkuat pemahaman mereka tentang pentingnya teknik yang benar dalam menjaga kebersihan gigi dan gusi (Failasufa, Fahrie and Arimbi, 2021;Hidayat et al, 2023;Mallineni et al, 2023;Oresti and Handiny, 2023;Utami et al, 2023).…”
Section: Hasil Dan Pembahasanunclassified